Promoter-proximal CTCF-binding promotes long-range-enhancer dependent gene activation - Kubo, Naoki (Nat Struct Mol Biol, 2021)
The CCCTC-binding factor (CTCF) works together with the cohesin complex to drives the formation of chromatin loops and topologically associating domains, but its role in gene regulation has not been fully defined. Here, we investigated the effects of acute CTCF loss on chromatin architecture and transcriptional programs in mouse embryonic stem cells undergoing differentiation to neural precursor cells. We identified CTCF-dependent enhancer-promoter contacts genome-wide and found that they disproportionally affect genes that are bound by CTCF at promoter and dependent on long-distance enhancers. Disruption of promoter-proximal CTCF binding reduced both long-range enhancer-promoter contacts and transcription, which are restored by artificial tethering of CTCF to the promoter. Promoter-proximal CTCF binding is correlated with transcription of over 2,000 genes, across a diverse set of adult tissues. Taken together, our study shows that CTCF binding to promoters may promote long-distance-enhancer dependent transcription at specific genes in diverse cell types.